Two alternatively-spliced human nebulin isoforms with either exon 143 or exon 144 and their developmental regulation - Lam, Le Thanh (Sci Rep, 2018)
Nebulin is a very large protein required for assembly of the contractile machinery in muscle. Mutations in the nebulin gene NEB are a common cause of nemaline myopathy. Nebulin mRNA is alternatively-spliced so that each mRNA contains either exon 143 or exon 144. We have produced monoclonal antibodies specific for the regions of nebulin encoded by these two exons, enabling analysis of expression of isoforms at the protein level for the first time. All antibodies recognized a protein of the expected size (600–900 kD) and stained cross-striations of sarcomeres in muscle sections. Expression of exon 143 is developmentally-regulated since newly-formed myotubes in cell culture expressed nebulin with exon 144 only; this was confirmed at the mRNA level by qPCR. In fetal muscle, nebulin with exon 143 was expressed in some myotubes by 12-weeks of gestation and strongly-expressed in most myotubes by 17-weeks. In mature human muscle, the exon 144 antibody stained all fibres, but the exon 143 antibody staining varied from very strong in some fibres to almost-undetectable in other fibres. The results show that nebulin containing exon 144 is the default isoform early in myogenesis, while regulated expression of nebulin containing exon 143 occurs at later stages of muscle development.